A numerical investigation of the mechanism of air-injection drag reduction. (January 2020) - Zhao, Xiaojie; Zong, Zhi; Jiang, Yichen; Sun, Tiezhi
Abstract: In order to investigate the mechanism of air-injection drag reduction, two different CFD models in OpenFOAM including the Eulerian-Eulerian two-fluid model and VOF model have been applied to study the there-dimensional drag reduction of an axisymmetric body by air injection. The calculated drag reduction rates obtained from the two models are compared against the experimental measurements. It is found that the numerical results from these two models agree well with the experimental data in two kinds of drag reduction regions: microbubble drag reduction (MBDR or BDR) region and air layer drag reduction (ALDR) region. For the transition region between BDR and ALDR, the data-coupling method based on the air flow ratio is proposed to calculate the drag reduction rates and the final coupling drag reduction rates are in well concordance with the experimental data under various air flow ratios. It is indicated that the CFD models presented in this study can be treated as good candidates to investigate the phenomenon of air-injection drag reduction. In addition, the predicted morphology of the mixture flow and air void fraction distributions around the body are also presented to provide valuable insights on this complex physical phenomenon. Based on the numerical results, it is found that in BDR region the air void fraction around the body can be considered as an important factor influencing the drag reduction, and in ALDR region the formation area of the air layer around the body surface will directly influence the drag reduction. For BDR, bubble size distribution and the effects of bubble size on drag reduction have been also investigated. In the end, the mechanism of air-injection drag reduction has been analyzed.